Colonial Philippines in Italian travel writing "Italians" interpreting difference - Melchor, Jillian Loise 1994- (Routledge focus on literature, 2024)
"The first comprehensive review of all extant 'Italian' chronicles set in the Philippine Islands, this book juxtaposes 'Filipino' Otherness with the unique condition of 'Italian' ambivalence and alterity within Europe. This book's contribution to the critical studies of travel is the opening of an analytical middle ground, highlighting the ambivalence of Italian chroniclers while acknowledging their participation in epistemological practices subsumed within the broader enterprise of conquest. Beyond the role of travel writing in colonial episteme, the book also situates the act of writing about one's travels in instances of national character building (in Italy's case) and in attempts of constructing a national historiography (in the Philippine case). This manner of nuancing literary productions by the West while navigating its implications in the East, specifically, how pre-Unification "Italian" travel informed nationalist constructions in the Revolutionary Philippines, could enrich our understanding of and refract monolithic conceptions of metropole-periphery relations"--